ESTABLISHING OF AQUATIC PROTECTED AREAS (APAS) NETWORK IN PAPUA'S BIRD HEAD'S SEASCAPE (BHS): SPECIES MIGRATION AND GENETIC CONNECTIVITY - Roni Bawole; Rony Megawanto (COJ (Coastal and Ocean Journal), 2017)
In general, the APAs network serves to protect, conserve and utilize marine resources in order to ensure sustainability is guaranteed on an ongoing basis. The APAs network is a network involving the management of two or more APAs (Kaimana, Fakfak, Bintuni, Raja Ampat, Sorong, Tambrauw and Teluk Wondama) synergistically linked to biophysical, species migration and genetic connectivity. From the biophysical aspect, BHS is characterized by migration and the specific habitat of endangered charismatic species and genetic connectivity. Migration in the BHS region can be seen from the migration of turtles, sharks, sharks, manta rays and cetaceans (whales and dolphins). The endangered species are unique in BHS and they utilize BHS area as a migration path and as an aggregation area. The world's largest leatherback turtle nesting beaches are also found in BHS, including other species of turtle nesting, such as green turtle, olive ridley turtle, and hawksbill turtle. Other charismatic species often found in the BHS region are manta rays, whale sharks, dugongs, and other endemic fish species. The BHS region is a cetacean hotspot that supports populations of species protected by the IUCN Red List. Of the 30 species of cetaceans recorded in Indonesia, 15 species are found in BHS. The whales can also migrate from Cenderawasih Bay to Raja Ampat Waters. Manta rays are often found in Raja Ampat, Yapen Island, and Cenderawasih Bay. Good collaboration is required in protecting species and understanding oceanographic phenomena that relate to the migration and genetic connectivity of the organism. Keywords Conservation network, bio-physical aspect, species migration, genetic connectivity, Bird's Head Seascape